Fraud Risk Management in Life Insurance: Challenges and Control Strategies in the Digital Age - Daimah; Siti Ainul Kholipah (Jurnal Indonesia Sosial Sains, 2026)
The development of digital technology has driven significant transformations in the life insurance industry, especially in the process of marketing, policy administration, and claims management. Digitalization provides operational efficiency and ease of service, but at the same time increases the complexity of the risk of life insurance fraud. Fraud is no longer limited to conventional practices, but is thriving in the form of digital data manipulation, identity forgery, and collusion that exploits the weaknesses of technological systems. This condition makes fraud risk management a strategic issue that needs to be studied in depth, especially in the context of life insurance in the digital era. This research aims to analyze the challenges of fraud in life insurance and identify risk control strategies implemented in the digital era. This study used a qualitative approach with a case study design. Data was collected through in-depth interviews with management, questionnaires open to licensed employees, and observations of operational processes and internal control systems. The results of the discussion show that digitalization improves service efficiency, but also widens the gap in fraud risk if it is not balanced with adequate control. The main challenges identified include limited human resource competencies, the lack of optimal use of data-based fraud detection technology, and weak internal control culture. The findings of the study also show that there is a gap in perception between management and operational employees regarding the level of fraud risk. The conclusion of this study confirms that life insurance fraud risk management in the digital era requires an integrated approach between technology, governance, and human resource development. Strengthening the internal control system and implementing digital-based preventive strategies are key to mitigating fraud risks in a sustainable manner.